Efforts to improve literacy at MTs N 6 Sleman - Moch Nur Hidayat (Yayasan Azhar Amanaa Yogyakarta, 2024)
MTs N 6 Sleman has a strong background in efforts to improve literacy in the madrasah. With a high commitment, structured curriculum, good library, parental involvement, and diverse literacy activities, the madrasah aims to create literate and competitive students in meeting the challenges of the future. The uniqueness of MTs N 6 Sleman has intrigued researchers to study the comprehensive and structured efforts undertaken by the madrasah to instill a spirit for literacy growth in the madrasah community. This research will employ a qualitative descriptive research design. Descriptive research is conducted to depict the actual conditions of a variable that is not clearly understood, using collected data and making systematic and accurate analytical conclusions. The efforts made by MTs N 6 Sleman to enhance literacy go through three stages: (1) Familiarization stage through enjoyable reading activities in the madrasah, (2) Development stage of reading interest, and (3) Implementation stage of literacy-based learning.